2018
DOI: 10.1002/jcp.26796
|View full text |Cite
|
Sign up to set email alerts
|

Chronic phosphodiesterase type 5 inhibition has beneficial effects on subcutaneous adipose tissue plasticity in type 2 diabetic mice

Abstract: Different adipose tissue (AT) depots are associated with multiple metabolic risks. Phosphodiesterase type 5 (PDE5) is involved in adipocyte physiology and PDE5 inhibition may affect adipogenesis and ameliorate white AT quality. The aim of this study is to investigate the distribution of AT and the composition of the stroma-vascular fraction (SVF) of subcutaneous AT (SAT) in type 2 diabetic mice after prolonged treatment with a PDE5 inhibitor, Sildenafil. 18 db/db mice were treated with Sildenafil or vehicle fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…These findings were then confirm in T2DM patients where 3 months of oral sildenafil (100 mg/day) reduced the endothelial function marker P‐selectin 49 . In pre‐clinical, as well as in clinical studies using chronic PDE5i with sildenafil 100 mg daily, we and others have shown that the NO‐cGMP‐PDE5 pathway and related targets are involved in the pathogenesis of several complications of diabetes affecting the immune system, 46‐48 adipose tissue, 50,51 and renal function 39 . A dose of 50mg of Sildenafil, given twice a week, was shown to improve surrogate markers of endothelial function (C‐reactive protein, endothelin‐1 and ICAM‐1, ANG‐1/TIE2 axis), modulating the number of circulating proangiogenic cells and exerting an anti‐inflammatory response in T2Dm patients 52 …”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…These findings were then confirm in T2DM patients where 3 months of oral sildenafil (100 mg/day) reduced the endothelial function marker P‐selectin 49 . In pre‐clinical, as well as in clinical studies using chronic PDE5i with sildenafil 100 mg daily, we and others have shown that the NO‐cGMP‐PDE5 pathway and related targets are involved in the pathogenesis of several complications of diabetes affecting the immune system, 46‐48 adipose tissue, 50,51 and renal function 39 . A dose of 50mg of Sildenafil, given twice a week, was shown to improve surrogate markers of endothelial function (C‐reactive protein, endothelin‐1 and ICAM‐1, ANG‐1/TIE2 axis), modulating the number of circulating proangiogenic cells and exerting an anti‐inflammatory response in T2Dm patients 52 …”
Section: Introductionsupporting
confidence: 64%
“…[46][47][48] These findings were then confirm in T2DM patients where 3 months of oral sildenafil (100 mg/day) reduced the endothelial function marker P-selectin. 49 In pre-clinical, as well as in clinical studies using chronic PDE5i with sildenafil 100 mg daily, we and others have shown that the NO-cGMP-PDE5 pathway and related targets are involved in the pathogenesis of several complications of diabetes affecting the immune system, [46][47][48] adipose tissue, 50,51 and renal function. Its expression in men 53 is even higher, making them more responsive to PDE5i, as revealed in pulmonary hypertension (PH) and fibrosis.…”
Section: Introductionmentioning
confidence: 95%
“…In this context, PDE5i treatment was indeed associated with a significant reduction of albuminuria and glycated hemoglobin (HbA1c) [60]. It is worth noticed that, some years later, a meta-analysis on the effect of PDE5i on glycemic control in T2DM concluded that PDE5i had no beneficial effect on HbA1c [61], similar results were obtained in diabetic mice, where the authors did not observed changes in blood glucose or insulin levels upon chronic inhibition of PDE5 [62].…”
Section: Endothelial Dysfunction and Inflammationmentioning
confidence: 69%
“…In db/db mice, sildenafil induced an overall reduction in AT, mainly in visceral AT (VAT) associated with a reduction in cytokines expression. Stromal vascular fraction (SVF) of subcutaneous adipose tissue (SAT) showed an increase in the frequency of anti-inflammatory M2 macrophages and endothelial cells in treated mice that leads to an improvement of SAT homeostasis and distribution [62] confirming an interconnection between inflammation and endothelium.…”
Section: Endothelial Dysfunction and Inflammationmentioning
confidence: 93%
“…GCTTGGTCTTGAATGAAGTCA, successfully demonstrated that udenafil suppresses TLR4 mRNA expression in the hypothalamus [9]. Another study conducted by Fiore et al (2018) with sequence forward: GGAGGAGAATACTGGCAAGA, reverse: GATGCATGGTAAGACAGGAC; in type 2 diabetic mice administrated sildenafil for 12 weeks could increase adipogenesis and improve adipose tissue [10]. The amplification of PDE5 gene depends not only on the primers determined, but it also depends on other factors such as dNTP, PCR templates, number of cycles, polymerase enzymes, and technical and non-technical effects [11].…”
Section: Introductionmentioning
confidence: 97%